Three-Dimensional Partonic Structure of the Nucleon - M. Anselmino (IOS Press, 2014)
The three-dimensional nucleon structure is central to many theoretical and experimental activities, and research in this field has seen many advances in the last two decades, addressing fundamental questions such as the orbital motion of quarks and gluons inside the nucleons, their spatial distribution, and the correlation between spin and intrinsic motion. A real three-dimensional imaging of the nucleon as a composite object, both in momentum and coordinate space, is slowly emerging.